Employee proactivity in organizations : an attachment perspective - Wu, Chia-Huei (Bristol shorts research., 2019)
Wu integrates the current understanding of motivational factors in shaping proactive workers, through his introduction to attachment theory, and development of it as a theoretical framework. This compelling approach provides academics with a new way of thinking about employee behaviour whilst also acting as a guide for practitioners and managers.